2022
DOI: 10.1111/ddi.13500
|View full text |Cite
|
Sign up to set email alerts
|

A hotspot of groundwater amphipod diversity on a crossroad of evolutionary radiations

Abstract: Aim: Groundwater harbours an exceptional fauna and provides invaluable ecosystem services, yet is among the least explored and consequently least protected ecosystems. Successful protection of its biodiversity depends on complete species inventories, knowledge of species spatial distribution, and quantification of biodiversity patterns, as well as disentanglement of the processes that shaped biodiversity patterns. We studied the hyper-speciose amphipod genus Niphargus as a model system within a global subterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 94 publications
2
27
0
1
Order By: Relevance
“…In this way, fragmentation of the terrestrial habitat and consequently of populations during the Pleistocene might have accelerated allopatric speciation (Pleistocene species pump) in terrestrial organisms, explaining part of the endemic diversity in this realm. A similar phenomenon likely drove Pleistocene speciation in amphipods, as recently proposed [ 94 ]. Therefore, differential impacts of Quaternary climate fluctuations and the resulting glaciations on different biomes and taxa go a long way in helping to explain extant patterns of diversity and endemism in the region.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this way, fragmentation of the terrestrial habitat and consequently of populations during the Pleistocene might have accelerated allopatric speciation (Pleistocene species pump) in terrestrial organisms, explaining part of the endemic diversity in this realm. A similar phenomenon likely drove Pleistocene speciation in amphipods, as recently proposed [ 94 ]. Therefore, differential impacts of Quaternary climate fluctuations and the resulting glaciations on different biomes and taxa go a long way in helping to explain extant patterns of diversity and endemism in the region.…”
Section: Discussionsupporting
confidence: 63%
“…Unlike fish, endemic amphipods, the second fully aquatic taxon in our data, emerged during or above all before the Pleistocene. Amphipod radiations in Europe are known for being rather ancient, predating the Pleistocene [ 28 , 92 , 93 ], while the youngest radiations probably are from the Pleistocene [ 94 ]. This corresponds to the paucity of postglacial speciation noticed here for this group across the Alps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borko et al (2022) analysed biodiversity patterns of Niphargus using two biodiversity metrics, species richness and phylogenetic diversity, on a grid‐based approach in Western Balkans. They found that species richness does not predictably correlate with phylogenetic diversity.…”
Section: This Issuementioning
confidence: 99%
“…The potential determinants of the range sizes of aquatic subterranean species were explored using the subterranean amphipod genus Niphargus, a mega-diversified genus of the Western Palaearctic, with more than 500 described and undescribed species (Borko et al, 2022). Niphargus species differ in their ranges; some are narrowly distributed or even single-site, and some have exceptionally large ranges extending over 1000 km (Copilas ¸-Ciocianu et al, 2017;Bregovi c, Fišer & Zagmajster, 2019).…”
Section: Introductionmentioning
confidence: 99%